2007
DOI: 10.3354/dao01877
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of the salmonid parasite Parvicapsula minibicornis (Myxozoa) in the Klamath River basin (Oregon-California, USA)

Abstract: The distribution and abundance of the myxosporean parasite Parvicapsula minibicornis in the Klamath River mirrored that of Ceratomyxa shasta, with which it shares both its vertebrate and invertebrate host. Assay of fish held at sentinel sites and water samples collected from those sites showed that parasite prevalence was highest below Iron Gate dam, which is the barrier to anadromous salmon passage. Above this barrier parasite levels fluctuated, with the parasite detected in the free-flowing river reaches bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In the adult sockeye, severe infection is associated with pathological changes in affected glomeruli and renal tubules (Raverty et al 2000). The parasite has also been reported from adult Pacific salmon in the Columbia and Klamath Rivers (Jones et al 2004, Bartholomew et al 2007, Atkinson et al 2011. Our detection of P. minibicornis confirms an earlier study in which the parasite was reported in juvenile Fraser River sockeye salmon in the Strait of Georgia.…”
Section: Discussionsupporting
confidence: 90%
“…In the adult sockeye, severe infection is associated with pathological changes in affected glomeruli and renal tubules (Raverty et al 2000). The parasite has also been reported from adult Pacific salmon in the Columbia and Klamath Rivers (Jones et al 2004, Bartholomew et al 2007, Atkinson et al 2011. Our detection of P. minibicornis confirms an earlier study in which the parasite was reported in juvenile Fraser River sockeye salmon in the Strait of Georgia.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the number of water-borne parasites in water samples may be considered an indirect indicator of infection risk or intensity, and real-time PCR analysis of water samples may prove useful as a novel method to replace the traditional use of susceptible host fish for both the detection and quantification of specific parasites [15,16,19-21]. In this study, as a preliminary study for pathogen monitoring of environmental water, DNA prepared from spore-suspensions was used in PCR assays.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated concentration of C. shasta has been documented in a stretch of the Klamath River main stem (Figure 1) [19], [20], [21], referred to herein as the “infectious zone”. Juvenile fall-run Chinook salmon are infected by the parasite while passing through this zone during their spring downstream migration to the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The spores of C. shasta that infect juvenile salmon are released from the polychaete Manayunkia speciosa , the secondary host of the parasite [19]. The infectious zone has a much greater density of infected polychaetes than surrounding locations [17], [21] although it is not yet clear why this is the case. It has been suggested that the polychaetes become infected by spores released during the fall and winter from carcasses of adult salmon that were infected while passing through the infectious zone during their upstream spawning migration [17], [19].…”
Section: Introductionmentioning
confidence: 99%